Edukasi Penerapan Teknik Akupresur Dalam Meningkatkan Imunitas Tubuh Pada Siswa Di SMK Pab-3 Medan Estate - Afina Muharani Syaftriani; Ani Rahmadhani Kaban; Maya Ardilla Siregar (STIKES Columbia Asia Medan, 2024)
The body's immunity is a system that works against foreign substances entering the body. The body's immunity must be well maintained so that it is not easily attacked by disease. Nurses can help people to increase their immune system by using complementary modalities. One of the complementary modalities that can be taught and is easy to do is the acupressure technique. Acupressure is a health method of applying pressure/massage to the surface of the skin which is expected to increase blood circulation, reduce tension and stress. The aim of implementing this community service is to provide education on the application of acupressure techniques to increase body immunity for students at SMK PAB-3 Medan Estate. The method used in carrying out this community service is by providing education through lectures and providing leaflets containing educational material at SMK PAB-3 Medan Estate. The targets for implementing the activities are students at SMK PAB-3 Medan Estate. The results of this community service have had a positive impact on the parties involved, especially for students at SMK PAB-3 Medan Estate. Students can increase their knowledge about the immune system in the body and how to increase the body's immunity with acupressure techniques as one of the complementary treatments. Apart from that, students can also improve their skills in increasing body immunity with acupressure techniques at points Li-4, PC6, and SP-6.